Examination of the Social and Gender Factor among Students Who Participated in Underwater Summer Camp - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2015)
The purpose of the present research is aimed at examining the effect of students' socio-cultural and economic structures and their genders on their opinions about the underwater summer camp in terms of social gender concept using survey method. A total of 40 volunteers among the students participated. In addition, the researchers examined students' reasons for preferring the underwater summer camp, and their opinions about the hotel, the boat and city of Marmaris where the camp was made. In the applied underwater summer camp, students were trained on scuba diving. The researchers examined subjects such as level of qualification between the students who participated in the camp in previous periods and the new participants; and students' interests in sports before they participated in the underwater sports summer camp. In the present study, frequency analysis which is a descriptive statistics method was used to determine distribution in terms of variables; then Mann Whitney-U test (unrelated samples t-test) which is a non-parametric test was used to determine the differences between variables formed by the participants' genders and their opinions about the underwater summer camp Average difference between variables was tested at a 0.05 significance level. According to these data, there are significant differences between the average number of family members who do other diving sports and gender; and the average of the effect of family members on the students' participation in the applied summer camp and their gender. However; significant difference was detected between gender and other variables. This finding indicates that underwater sports are open for improvement for both genders; especially for female individuals in the society.
Keywords: Socio-cultural; Social Roles; Economic Structure; Scuba Diving; Recreation